Programa autónomo de evaluación térmica para procesadores Intel® - Treminio Moreno, Guillermo (Instituto Tecnológico de Costa Rica, 2005)
Intel® Corporation of Costa Rica is dedicated to assembly and test different electronic products, including microprocessors. After the assembly process, the processor is tested for the purpose of giving guaranteed products to the client. Thermal Tests are included in this set of test that the processor has to pass, being the temperature a determining factor of the performance of any processor. When the processors are distributed to different companies dedicated to assemble computers, for example DELL, HP, IBM, etc., the processors are tested by them with tests not validated by Intel® and this causes that the processors in good thermal conditions are sent back to Intel’s facilities to be reviewed. This revision of good processors means lost of time and resources to the company. The objective of the present project is to develop a software able to carry out thermal evaluations to different processors from any personal computer, which will allow, to the different clients of Intel®, perform a validated thermal test to the processors from their facilities. In order to implement this project the Thermal Control Circuit integrated on the surface of the processor will be used. This circuit activates when the temperature of the processor reaches a critical value. The software will be able to call an application that operates the processor in extreme form, causing it to be warmed up until this circuit is activated. The time that lasts between the beginning of the test and the activation of the circuit will determine the thermal performance of the processor.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2005
Keywords: Enfriamiento; Temperatura; Voltaje; Frecuencia; Control; Monitoreo